Desorption characteristic of LiBr–H2O solution in hydrophobic hollow fiber membrane for absorption chiller. (August 2021) - He, Jiacheng; Hirata, Ryusuke; Hihara, Eiji; Dang, Chaobin
Highlights: A PTFE membrane module is used as a desorber in an absorption refrigeration system. Water vapor transports through a hollow fiber membrane by Knudsen diffusion. A concentration difference of about 0.4% is achieved with a tiny membrane desorber. Abstract: The membrane-based desorber is considered a promising alternative to miniaturize the present generator in the absorption refrigeration system, owing to its large specific interfacial area, which is expected to reduce the required volume for the unit of cooling capacity of the system. The heat and mass transfer characteristics of a desorber consisting of a porous polytetrafluoroethylene hollow fiber membrane were evaluated by both experiment and simulation under practical working conditions. The Knudsen diffusion was verified by a gas permeability test prior to the water vapor desorption test. According to the desorption experiment results of the LiBr-H2 O solution, a concentration difference of approximately 0.4% was achieved under the investigated conditions. The results also indicated that an increase in the solution flowrates leads to an increase in the water vapor desorption rate owing to the increase of sensible heat. The compared simulation and experimental results were consistent with an acceptable accuracy. This study provides a fundamental understanding of the heat and mass transfer of the membrane-based desorber, which benefits the design of the compact membrane-based absorption refrigeration systems.